A new configuration of Geiger-type cable domes with sliding ridge cables: Computational framework and structural feasibility investigation. (1st July 2023) - Xue, Yu; Luo, Yaozhi; Wang, Yafeng; Xu, Xian; Wan, Hua-Ping; Shen, Yanbin; Fu, Wenwei
Highlights: A new configuration of Geiger-type cable domes with sliding continuous ridge cables is proposed. A general energy-based computational framework is proposed for the analysis of the structure. The new cable dome has better construction features and feasible mechanical properties. Abstract: Cable domes have been widely used in the field of structural engineering for their lightweight feature that is fit for large-span structures. Geiger-type cable domes have gained much attention due to their simple configurations. This paper proposes a modified Geiger-type cable dome with sliding ridge cables. Compared to conventional forms, the pre-stresses in the cables are more uniform, and the number of cables is fewer. An energy-based method is adopted to derive the equilibrium equations for the form-finding and load response analysis of the sliding cable system. The Levenberg-Marquardt algorithm is used to solve the non-linear equilibrium equations. A numerical example is employed to demonstrate the feasibility of the proposed structural form in terms of structural strength, stiffness, and stability. The influence of two design parameters, i.e., the force ratio of the hoop and ridge cables and the strut length, on the structural performance is investigated. In general, the new cable dome has better construction features and feasible mechanical properties and is believed to have the potential for practical applications.